Impact of COVID-19 on Antenatal, Natal, and Postnatal Care of pregnant females at Akbar Niazi Teaching Hospital - Nadia Jabeen, Fareeha Zaheer, Kinza Ali, Amna Faruqi, Irfan Afzal Mughal, Asma Irfan, Nadia Jabeen, Fareeha Zaheer, Kinza Ali, Amna Faruqi, Irfan Afzal Mughal, Asma Irfan (Journal of Rawalpindi Medical College, 2021)
Objective: To determine the perception of pregnant patients regarding the COVID pandemic, preventive measures taken by the patients during the pandemic, and the impact of COVID on their Natal, Intrapartum, and Postpartum Care. Materials and Methods: This study included 850 patients presenting in the Obstetrics and Gynaecology department for antenatal care, inpatient care (delivery and caesarean section), and postpartum complications. Percentages were calculated for descriptive variables like demographic factors, source of information, and opinion of patients about COVID-19, preventive measures are taken by the patients, their Antenatal, Natal, and Postnatal fears. An independent t-test was applied and a p-value of ˂0.05 was taken as statistically significant. Results: We enrolled 850 patients in this study with a mean age of +28 years,mean gravidity of +3, 50% were matriculated and 75% of our patients belonged to middle-class families.. Among our patients, 96% were in fear of getting infected along with their fetus, if they visited the hospital for antenatal care, which is why a majority of them did not visit the hospital for antenatal care and a statistically significant percentage (80%) of them missed antenatal care for 5 months. While the same number of patients (96%, p-value ˂0.05) shared their fear regarding contracting the infection from the hospital during delivery and postnatal care in the hospital, and the same percentage were of the opinion that the baby would get infected during and after delivery in a hospital. Conclusion: Antenatal care is a basic right of every pregnant female. During emergencies like pandemics ways and means should be devised, not only to provide care but, also, to address the fears of pregnant females to prevent complications during this important phase of life.